Effectiveness of Nursing Care Standard Training Through Enhancement Nurse's Knowledge in Applied - Thika Marliana; Agung Tri Nugraha; Rifki Heryandi; Jamiatun Jamiatun (GLOBAL HEALTH SCIENCE GROUP, 2022)
Knowledge results from a condition known with sensing to something object. Care nursing is an important process in providing quality care. The purpose _ of the study is to know the existence connection Among Knowledge nurses and an application of standard care nursing in patients at the Palabuhanratu Hospital, West Java. Research design quantitative with an approach Cross Sectional with an amount sample of 140 nurses. Test data analysis using Chi-Square. Research results in part big nurses have Higher Knowledge that is as many as 126 nurses (90.0%) and apply Standard Care Nursing Well that is as many as 123 nurses (87.9%). Statistical test results obtained p value = 0.015 then could conclude that there is a connection Between the knowledge of nurses and the application of standard care nursing at Palabuhanratu Hospital. Recommended could follow training in Standard care nursing to add outlook to the nurse and give appropriate service with standard care nursing.